เตรียมตัวอย่างไรให้ตายดี How to prepare for good death - วันศรี อุดมวรรณ; ประภาษานนท์ เยาวเรศ (Journal of The Royal Thai Army Nurses, 2014)
ความตายเป็นสิ่งที่เกิดขึ้นกับทุกคนและต่างปรารถนาที่จะตายดี คือ ตายอย่างสงบสบายไร้กังวล หลุดพ้นจากทุกสิ่ง ซึ่งแต่ละคนไม่มีใครรู้ว่าตัวเองจะตายเมื่อไหร่ ที่ไหน และตายอย่างไร ดังนั้น การเตรียมตัวช่วงดำเนินชีวิตและช่วงใกล้ตาย โดยประยุกต์หลักการ 5 ส. คือ สะสาง สะอาด สะดวก สุขลักษณะ และสร้างนิสัย และ 4 อ. คือ อาหาร อากาศ ออกกำลังกาย อารมณ์ โดยการจัดการด้านอาหาร อากาศ การออกกำลังกาย และอารมณ์ ด้วยการทำส. ตัวแรกคือ สะสางสิ่งที่ไม่ดีออกไป คงสิ่งที่ดีมีประโยชน์ไว้ตามด้วย ส. สะอาดของกายและจิตที่ละกิเลสลงเรื่อยๆ จนมีความเป็นอยู่ที่เรียบสบาย จากนั้นก็จะเป็น ส.สะดวก มีความคล่องแคล่วในการละสิ่งไม่ดี ทำแต่สิ่งดีที่สุด มีความพร้อมเผชิญความตาย และ ส. ตัวที่สี่คือ สุขลักษณะ เป็นการทำที่มีลักษณะถูกต้องดีงามเกิดความสงบสบายปลอดโปร่ง ส่วน ส. สุดท้ายคือ สร้างนิสัย ทำดีมีคุณและไม่ประมาทต่อความตายจนคุ้นชิน เมื่อถึงเวลาตายก็จะตายดีได้ Although death always happens to everyone without notifying, all prefer to good death. By most standards, a good death is one in which a person dies peaceful, carefree, comfortable, and releasing from everything. Since no one does not know exactly when, where, and, how his or her life end, planning for death is required during his or her life. There are five methods suggested to think about their deaths during life: clearing up, cleaning, comfort, hygienic practice, and temperament. For the first approach, clearing up means by eliminate the bad things and remain good things which follows by cleaning. This process is focusing on reducing desires from body and mind. If this way performs generally, it probably changes their life to be comfort which turning on the hygiene for being peaceful. Practicing on procedures will develop a goodcharacterwhich one will accept the truth that leads to a good death. Regarding for daily life practices, five techniques are modified by four conditions which normally operate everyday activities as such as food, air, exercise, and emotion.